Challenging heteronormativity and reimagining transnormativity: the lived experiences of filipino cisgender men in monogamous romantic relationships with transgender women - Prudenciado, Renz; Doneys, Philippe; Chatterjee, Joyee S.; Kusakabe, Kyoko; Deutscher Akademischer Austausch Dienst (DAAD), Germany (Pathum Thani, Thailand : Asian Institute of Technology, 2023)
In a world where love is both a complex emotion and a societal construct, the stories of five Filipino cisgender men and their transgender partners{u2014}living in Metro Manila, Philippines{u2014}challenge heteronormative perspectives of romantic relationships{u2014}eclipsing traditional gender norms to redefine masculinity. An intimate journey through semi-structured in-depth interviews and thematic analysis conducted in the first quarter of 2023 provides chart milestones of a newly spanning landscape of transnormativity and new masculinity in the romantic relationships they share. Despite transphobia and rejection being frequent features in transgender women's life, men embrace the fluid definitions of beauty and gender identity, irrespective of anatomical structures. They recognize and value the subjective beauty and femininity of their partners without the need for gender-affirming surgeries. These men form bonds with their partners through caregiving and affection, accepting to serve as homemakers and shedding their alpha-male exterior to embrace their partners' needs. While they prefer to act as primary economic providers, they do not take it as a threat to their masculinity when their partners earn more and share financial responsibilities with them. Communication is crucial in building healthy relationships, despite challenges such as inferiority complexes and the gender dysphoria of their partners and the COVID-19 pandemic. The families of these couples accept their relationships, reinforcing the transformative power of love that transcends traditional societal norms. However, hegemonic forms of masculinity and gender policing within the relationships can still reinforce sexual inequality, male dominance, and female subordination. Negotiations around what women should wear or present in public can lead to pariah femininity and slut-shaming. The love stories of these Filipino cisgender men and their transgender partners call the need for Civil Union Law in the Philippines{u2014}advancing Gender Equality and Peace Development from home and beyond.
A thesis submitted in patial fulfillment of the requirements for the degree of Master of Science in Gender and Development Studies
Thesis (M. Sc.) - Asian Institute of Technology, 2023
Keywords: Transgender people -- Attitudes -- Philippines; Interpersonal relations -- Philippines; Man-woman relationships -- Philippines